PENYULUHAN LITERASI DIGITAL (FINTECH) BAGI GURU DAN SISWA/I MAN 1 PULAU HARAPAN, KEP. SERIBU, JAKARTA - Badie Uddin; Abdul Karim; Ibnu Suryadi (POLITEKNIK LP3I JAKARTA, 2024)
The development of financial literacy is very rapid because of digital technology which makes it possible for all groups to access various kinds of financial services. Even though the OJK regulator has implemented quite strict age limits and requirements in accessing these financial facilities, many of the general public, especially students who already have ID cards, ignore the terms and conditions in accessing these financial services, this has an impact on the phenomenon of many students who entangled in online loans, and even e-commerce transactions that make it easier for people to get into debt, this service tries to provide counseling or outreach to the public, especially students, to better understand financial literacy and to thoroughly examine the impacts and benefits. The student chosen as the object of this service is MAN 1 Pulau Harapan, Kep Seribu, Jakarta. The methods used in this community service activity are training, lectures and questions and answers, and discussions. The result of this activity is to increase knowledge of digital financial literacy for teachers and students/I MAN I Pulau Harapan Kep Seribu.. The conclusion of this activity is very useful for students in understanding digital finance in terms of advantages and disadvantages.